Priority‐Based QoS Aware Routing Protocol for Wireless Body Area Networks - Rahimi, Abdollah; Shahbazzadeh, Mehdi Jafari; Khatibi Bardsiri, Amid (International journal of communication systems, 2025)
ABSTRACT With the progress of technology in the field of wireless communication, wireless body area networks (WBANs) have been introduced. WBANs consist of a number of intelligent biomedical sensor nodes and a special node called sink. Sensors are placed on the patient's body or under the skin, and their task is to check physiological parameters and report to the sink. The resources of these nodes are limited, and communication is subject to various issues. Maintaining the quality of communication due to the high importance of the transmitted data and severe limitations is one of the important issues in WBANs. The important challenge in this area is designing a framework for next‐hop node selection with covering the quality needs of the transmitted data. This paper proposes a Priority‐Based QoS Aware Routing Protocol for WBANs (PQARP). PQARP is a three‐step method. In the first step, the sensors are configured. In the second step, data is separated and marked. In the third step, the proposed PQARP routing is done and the most appropriate intermediate node is selected to send data. The simulation results using NS‐2 showed the remarkable capabilities of PQARP in covering quality requirements of different data sent and improving the metrics of end‐to‐end delay, successful delivery ratio, throughput and energy consumption compared to other similar methods. The proposed method is designed to improve the routing and communication of WBANs and its main contribution to achieve this goal is as follows: (1) Providing the ability to analyze and recognize the type of data sent; (2) Proposing a mechanism for adaptive routing in order to support QoS of different data (normal, emergency and on‐demand data); (3) Improving next hop selection and QoS based on the use of TOPSIS technique and focusing on multi‐metric evaluation; (4) Supporting the optimization of energy consumption in line with QoS.